2020
DOI: 10.2147/ott.s278013
|View full text |Cite
|
Sign up to set email alerts
|

<p>Progress in Understanding the IL-6/STAT3 Pathway in Colorectal Cancer</p>

Abstract: As a pleiotropic cytokine, interleukin-6 (IL-6) not only regulates the cellular immune response, but it also promotes tumor development by activating multiple carcinogenic pathways. IL-6 expression is significantly elevated in colorectal cancer (CRC) and is closely related to CRC development and patient prognosis. In CRC, IL-6 activates signal transducers and activators of transduction-3 (STAT3) to promote tumor initiation and tumor growth. IL-6/STAT3 signalling has a profound effect on tumor-infiltrating immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 89 publications
2
79
0
Order By: Relevance
“…To validate the above findings, we selected the COL1A1 and IL-6 for further study and detected whether they were co-expression in glioma tissues. IL-6, as an important immunosuppressive and immunosuppressive cell recruitment factors, has a profound effect on immune cell infiltration in the tumor immune microenvironment [ 28 , 29 ]. The double-immunofluorescence staining revealed that the co-expression of COL1A1 with IL-6 was found in WHO II-IV grade glioma tissues (Additional file 6 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To validate the above findings, we selected the COL1A1 and IL-6 for further study and detected whether they were co-expression in glioma tissues. IL-6, as an important immunosuppressive and immunosuppressive cell recruitment factors, has a profound effect on immune cell infiltration in the tumor immune microenvironment [ 28 , 29 ]. The double-immunofluorescence staining revealed that the co-expression of COL1A1 with IL-6 was found in WHO II-IV grade glioma tissues (Additional file 6 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 expression induces CRC invasion via the upregulation of integrin β 6 through the IL-6 receptor/STAT-3 signaling [ 103 ]. Several clinical studies have been conducted targeting the IL-6 pathway in CRC; however, no significant anticancer effects have been observed yet with IL-6 monoclonal antibodies alone [ 104 , 105 , 106 , 107 ].…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…Several types of therapeutics are available, such as anti-IL-6 or anti-IL-6R antibodies, soluble gp130Fc (sgp130Fc), and selective small-molecule JAK inhibitors, that are used in the treatment of human diseases [ 38 , 74 ]. An IL-6 inhibitor, siltuximab, has been studied in a phase II and III clinical trial (NCT00841191); no clinical activity was observed when the drug was used as a monotherapy, but it was well-tolerated [ 75 ].…”
Section: Clinical Studies On Drugs Targeting Il-6 Signaling For Crc Therapymentioning
confidence: 99%